HUBUNGAN TINGKAT PENGETAHUAN SUAMI TERHADAP PEMBERIAN IMUNISASI PADA BAYI DI PUSKESMAS MAYOR UMAR DAMANIK TAHUN 2019. - MALLISA JUNI AISYAH HASIBUAN (LP2MTBM MAKARIOZ, 2020)
is immunity in infants against various diseases, so that infants and children grow up in a healthy state. Immunization is a precaution so that the body is not affected by certain infections such as tetanus, whooping cough (pertussis), measles (measles) poliodan tubercoluse, or if terkenapun, not giving fatal consequences for the body. This study aims to identify the correlation between husband knowledge with emotional support to immunization in infants using descriptive design koleratif. The study sample as many as 38 husbands who have babies aged 3 to 11 months in the village sipagimbar. Determination of the number of samples based on the total sampling. The results of the study with fisher’s Exact Test i showed significant correlation between husband knowledge about immunization with emotional support to immunization in infants with p = 0.05 Of the 38 respondents 68.4% had sufficient knowledge and 31.6% of respondents had a good knowledge of 73.7%, less support is categorized and 26.3% for both categories of support. It is expected to conduct research on the correlation between husband knowledge with emotional support to immunization in infants in a different place with a number of the larger population in order to complement this research